The Influence Of Principal Leadership On Teacher Performance At SMA Negeri 1 Watubangga - Neli Pramawati; Arafat; Ahmad Farouq Mulku Zahari (Perkembangan Kajian Sosial, 2026)
This study seeks to understand how a school principal’s leadership affects teacher performance at Watubangga State High School 1. This study is a type of quantitative study. Information was gathered through watching, questionnaires, and school records. All 39 teachers at Watubangga State High School 1 participated in this study, and everyone was included in the sample. The data were examined using basic statistics and a simple linear regression test with SPSS version 25 to see the links and effects between the principal’s leadership (X) and teacher performance (Y). The results of this study, based on hypothesis testing, show that the principal’s leadership greatly affects how well teachers perform. This was shown using the F test, where the calculated F value of 36.422 was higher than the F table value of 4.10 with a significant of 0.000 < 0.05. The t-test also indicated that the calculated t-value of 6.12 was greater than the t-table value of 1.665, This implies that principal leadership has a partial impact on teacher performance. According to the coefficient of determination (R Square) of 0.582, principal leadership has an impact on 58.2% of teacher performance, and the remaining 41.8% is influenced by other factors not discussed in this study research.